Spatiotemporal Mislocalization of Nuclear Membrane-Associated Proteins in γ-Irradiation-Induced Senescent Cells - Svobodová Kovaříková, Alena; Bártová, Eva; Kovařík, Aleš; Lukášová, Emilie (Cells, 2020)
Cellular senescence, induced by genotoxic or replication stress, is accompanied by defects in nuclear morphology and nuclear membrane-heterochromatin disruption. In this work, we analyzed cytological and molecular changes in the linker of nucleoskeleton and cytoskeleton (LINC) complex proteins in senescence triggered by γ-irradiation. We used human mammary carcinoma and osteosarcoma cell lines, both original and shRNA knockdown clones targeting lamin B receptor (LBR) and leading to LBR and lamin B (LB1) reduction. The expression status and integrity of LINC complex proteins (nesprin-1, SUN1, SUN2), lamin A/C, and emerin were analyzed by immunodetection using confocal microscopy and Western blot. The results show frequent mislocalization of these proteins from the nuclear membrane to cytoplasm and micronuclei and, in some cases, their fragmentation and amplification. The timing of these changes clearly preceded the onset of senescence. The LBR deficiency triggered neither senescence nor changes in the LINC protein distribution before irradiation. However, the cytological changes following irradiation were more pronounced in shRNA knockdown cells compared to original cell lines. We conclude that mislocalization of LINC complex proteins is a significant characteristic of cellular senescence phenotypes and may influence complex events at the nuclear membrane, including trafficking and heterochromatin attachment.
Keywords: stárnutí buněk; heterochromatin-nuclear membrane disconnection; Lamin B Receptor; SUN1/2; časoprostorová analýza; Receptors, Cytoplasmic and Nuclear; membránové proteiny; Membrane Proteins; Cellular Senescence; LINC complex proteins; Gamma Rays; lidé; Humans; Nuclear Envelope; lamin B receptor; receptor laminu B; γ-irradiation; jaderný obal; Spatio-Temporal Analysis; receptory cytoplazmatické a nukleární; záření gama; nesprin-1